2007
DOI: 10.1111/j.1540-6237.2007.00457.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonprofit Advocacy Organizations: Their Characteristics and Activities*

Abstract: In this article we examine political advocacy by nonprofit organizations. Relatively little is known about the types of organizations that participate in advocacy, their characteristics, the issues for which they advocate, and the resources they devote to it. This is especially the case for nonprofits that operate at the state or local level. Copyright (c) 2007 Southwestern Social Science Association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
171
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(180 citation statements)
references
References 29 publications
6
171
3
Order By: Relevance
“…Some authors have defined all organizations in their studies with 501(c)(3) status as charitable or social service groups (e.g., Child and Gronbjerg 2007;Leech 2006). Defining charitable organizations in this manner, however, excludes a large number of groups with charitable missions that employ both 501(c)(3) and 501(c)(4) statuses in an effort to avoid IRS lobbying, and in some cases, electioneering restrictions.…”
Section: Measuring Lobbying and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors have defined all organizations in their studies with 501(c)(3) status as charitable or social service groups (e.g., Child and Gronbjerg 2007;Leech 2006). Defining charitable organizations in this manner, however, excludes a large number of groups with charitable missions that employ both 501(c)(3) and 501(c)(4) statuses in an effort to avoid IRS lobbying, and in some cases, electioneering restrictions.…”
Section: Measuring Lobbying and Analysismentioning
confidence: 99%
“…1 Studies of business lobbying have attempted to determine what percentage of the overall lobbying population is made up of for-profit corporations and business associations (e.g., Baumgartner and Leech 2001;Schattschneider 1960). Charitable lobbying studies, on the other hand, have examined populations of charities and attempted to determine what percentage engage in lobbying at all (e.g., Berry and Arons 2003;Child and Gronbjerg 2007). Studies of charities have almost uniformly concluded that many, if not most, charitable groups avoid formal advocacy.…”
Section: The Great Lobbying Dividementioning
confidence: 99%
See 1 more Smart Citation
“…However, most of this research has focused on Western democracies and on the role and efforts of CSOs (Appe and Layton 2016;Guo and Zhang 2014;Najam 2000;Smith 1984). Studies of legislative advocacy (Saidel 2002;Schmid, Bar, and Nirel 2008;Mosley 2010;Child and Grønbjerg 2007) have examined CSOs' organizational capacities and legal restrictions, and the impact of those factors on CSOs' legislative advocacy efforts, mainly in developed countries.…”
Section: Cso Advocacymentioning
confidence: 99%
“…Jenkins (1987, 324) sees advocacy as a "major force for the renewal of American democracy", and as an element counteracting interests of big business. Though most policy analysts and scholars of the nonprofit sector agree that nonprofit advocacy is a significant political component of the American nonprofit sector (Jenkins 1987;McNutt and Boland 1999;Child and Grønbjerg 2007), advocacy is a lopsided battle: one which entails pursuing public interests (Andrews and Edwards 2004) and a struggle to represent collective interests against powerful elite influences (McNutt 2008;Suárez 2009). This lopsidedness regarding the advocacy of often-vulnerable publics forms another impetus to increase awareness of the potential impact of nonprofit lobbying.…”
Section: Broader Concepts Of Nonprofit Lobbyingmentioning
confidence: 99%